Study of virgin coconut oil cost and yield by using natural method fermentation - Abd Rahman, Misbahul Muneer; Md Maarof, Mohd Zulariffin; Roslan, Muhammad Sufi; Fadzil, Muhammad Ihsanuddin; Noh, Nur Syaza Hanim; Kamalrulzaman, Muhammad Daniel Haikal (Penerbit UTHM, 2020)
Coconut has existed for at least thousands of years. Its flesh, its husk, its shell and its milk can be used for different purposes. Most importantly, coconut oil has been applied in numerous applications such as cosmetics, cooking ingredient and medicine. Coconut has been widely used in Southern and Central American regions, Asia, and Pacific regions. Its natural habitat is mostly on the tropical regions or along the beach shore. The ideal conditions for it to grow are with high humidity coupled with rainy and sunny weather. Countries such as Malaysia, Brunei, Sri Lanka, Indonesia, Philippines and Papua New Guinea are very significant with coconut cultivation. Coconut is very influential to the life of tropical people because they can derive the benefits in their daily use. Nowadays, the trend of using natural skincare is on the rise, according to the 12-months Google trend.